2021
DOI: 10.31083/j.ceog4806225
|View full text |Cite
|
Sign up to set email alerts
|

Emergency contraception knowledge level and e-health literacy in Turkish university students

Abstract: Background: Unwanted pregnancy is a serious problem, especially considering its impact on the lives of young people. Currently, emergency contraception (EC) is an effective method to prevent unwanted pregnancies that result in unsafe abortions and harm women's health. It is essential that university students, one of the risk groups for unwanted pregnancies, be familiar with this method. The aim of this study is to determine university students' knowledge of emergency contraception, influencing factors and e-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The identified studies used various types of health literacy related to the following health topics: general health31 32 34 35 42–67; nutrition68–82; non-communicable diseases (NCDs)36 63; HIV83 84; e-health39 85–91; media92; physical health93 94; oral health38 95; medical96; disability67 97 98; mental health37 40 41 99–108; suicide109 110; and depression 33 111. These studies used 36 scales to measure health literacy, and these scales can be grouped into three categories: newly developed scales66 77 82 86 93 98; newly adapted and translated scales33 40 41 43 54 55 64 69 83 96 100 111; and previously adapted and translated scales 34 35 38 39 44–46 49 51–53 56–59 62 65 67 68 71–73 76 78–80 85 87–89 91 95 97 103 104 107–110 112 113…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The identified studies used various types of health literacy related to the following health topics: general health31 32 34 35 42–67; nutrition68–82; non-communicable diseases (NCDs)36 63; HIV83 84; e-health39 85–91; media92; physical health93 94; oral health38 95; medical96; disability67 97 98; mental health37 40 41 99–108; suicide109 110; and depression 33 111. These studies used 36 scales to measure health literacy, and these scales can be grouped into three categories: newly developed scales66 77 82 86 93 98; newly adapted and translated scales33 40 41 43 54 55 64 69 83 96 100 111; and previously adapted and translated scales 34 35 38 39 44–46 49 51–53 56–59 62 65 67 68 71–73 76 78–80 85 87–89 91 95 97 103 104 107–110 112 113…”
Section: Resultsmentioning
confidence: 99%
“…Among the nine studies that addressed e-health literacy,39 85–91 113 a study including Iranian high school students noted a low level of e-health literacy 86. The other six studies were conducted in Turkey: four of them found that Turkish high school and midwifery students had a satisfactory level of e-health literacy39 88–90 whereas the other two found that university and college students had intermediate levels of e-health literacy 85 87.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The major factor limiting the use of EC may be inadequate information about their effectiveness and availability or unfavorable opinions and attitudes about their safety due to misinformation. Despite the fact that different modern contraceptives exist in Egypt, the problem of unintended pregnancy still present which could be due to gap in childbearing women's awareness regarding emergency contraception (28,29) .…”
Section: Significance Of the Studymentioning
confidence: 99%